(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Death is an unavoidable fate of human life. Medico-legal deaths are any unclear or vaguely suspicious deaths that require investigation. Women, who contribute about half of the population, have been harassed and exploited irrespective of their region and culture. Medico-legal death of Females is one of the indicators of level of social and mental health. This one-year study was thus undertaken to ascertain the various aspects of female medico-legal deaths in our region. In this study, the maximum number of female Unnatural deaths was seen in 3rd decade of life followed by 4th decade. Maximum numbers of accidental deaths were seen in the age group of 21 to 30 years, followed by 31 to 40 years. In female suicidal deaths, the most commonly affected age group was 11 to 20 years of age. The most common causes of female unnatural deaths were trauma followed by asphyxia and poisoning. The present study revealed that trauma mainly accidents is the major cause of unnatural deaths in females. To avoid unnatural female deaths, preventive measures should be adopted promptly wherever possible, like a safe driving culture, educating society to reduce accidental poisoning by agrochemicals, and psychological support to young females. If not preventable, prompt care should be provided to save the victim’s life.